2019
DOI: 10.5114/pq.2019.85150
|View full text |Cite
|
Sign up to set email alerts
|

The relation between cognitive impairment severity and postural stability in the elderly

Abstract: Introduction. The purpose of this study was to evaluate the relationship between the severity of cognitive impairment and the results of stabilographic tests in elderly patients with cognitive impairment. Methods. The study involved 42 participants aged 62-84 (mean 73.4 ± 6.7) years. The assessment of cognitive status was carried out with the Mini-Mental State Examination (MMSE). included were subjects who obtained a score below 27, which is the cutoff score between the absence and presence of cognitive impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
0
0
3
Order By: Relevance
“…Some of these are the angulations observed in the subtalar joint as a result of the increase in loading to the medial, and thus, the pronation of the foot. The excessive pronation observed in the foot, together with pes planus, causes biomechanical changes in the ankle, knee, and hip joint [25,28]. Agoada et al [26] showed that subtalar angle was correlated with excessive pronated foot and pes planus as it can be seen in this study.…”
Section: Discussionsupporting
confidence: 74%
“…Some of these are the angulations observed in the subtalar joint as a result of the increase in loading to the medial, and thus, the pronation of the foot. The excessive pronation observed in the foot, together with pes planus, causes biomechanical changes in the ankle, knee, and hip joint [25,28]. Agoada et al [26] showed that subtalar angle was correlated with excessive pronated foot and pes planus as it can be seen in this study.…”
Section: Discussionsupporting
confidence: 74%
“…Desde este punto, se hace necesario identificar, inicialmente, la importancia del control postural, entendido como la capacidad de poder controlar la posición del cuerpo en el espacio, determinada por una compleja interacción entre los sistemas musculoesquelético y neurológico (Cano de la Cuerda et al, 2016) y, que pretende conectar la relación entre la triada persona-tarea-entorno, para que el ser humano se mueva con un objetivo y sea funcional (Cieślik et al, 2019). Para lograr esta relación óptima, las FMS y los procesos psicológicos y comportamentales han sido destacados como aspectos fisiológicos fundamentales, debido al control superior que ejerce el SNC para poder generar movimiento controlado y voluntario.…”
Section: Control Postural Y Trastornos Mentalesunclassified
“…Di satu sisi, itu merupakan hasil dari tidak berfungsinya reseptor yang terlibat dalam proses menjaga keseimbangan. Di sisi lain, fenomena tersebut mungkin terkait dengan proses berpikir yang salah yang mengakibatkan pengambilan keputusan yang salah ketika berisiko jatuh (Cieślik et al, 2019). Pada penelitian yang dilakukan oleh Agrawal et al, (2020) mendemonstrasikan bahwa keterampilan kognitif spasial memburuk seiring dengan bertambahnya usia, yang mengarah pada kerusakan sistem vestibular.…”
Section: Hubungan Fungsi Kognitif Terhadap Keseimbanganunclassified